Designing an Integrated Information System with a Fast (Sister Fani) and Attractive Interface to Improve Performance and User Experience: Case Study at SMK PGRI 1 Tangerang - DIDI KURNAEDI (Komunitas Dosen Indonesia, 2024)
The Integrated Information System (Sister Fani) represents a significant innovation within the educational framework of SMK PGRI 1 Tangerang. Recognizing the imperative for a swift and engaging interface, this research endeavours to conceptualize and execute Sister Fani to adhere to elevated standards of performance and user satisfaction. Employing a qualitative methodology, data collection was facilitated through observation, interviews, and documentary research. The findings of this study underscore the pivotal role of a rapid and captivating interface design in enhancing user efficiency and enriching the overall user experience. By streamlining the process of accessing and utilizing information, the redesigned Sister Fani platform emerges as a catalyst for heightened productivity and improved service quality within the educational context of SMK PGRI 1 Tangerang. The practical implications of this research are manifold. The integration of Sister Fani into the operational framework of SMK PGRI 1 Tangerang promises to yield tangible benefits, including heightened productivity and enhanced educational service quality. By optimising the interface design to align with user expectations and requirements, educational institutions can cultivate an environment conducive to seamless information dissemination and utilisation. In conclusion, the successful implementation of Sister Fani stands poised to revolutionize the educational landscape of SMK PGRI 1 Tangerang, offering a paradigmatic shift towards efficiency, accessibility, and user-centricity.